Collection, pre-processing and on-the-fly analysis of data for high-resolution, single-particle cryo-electron microscopy. Issue 1 (January 2019) - Thompson, Rebecca; Iadanza, Matthew; Hesketh, Emma; Rawson, Shaun; Ranson, Neil
Abstract The dramatic growth in the use of cryo-electron microscopy (cryo-EM) to generate high-resolution structures of macromolecular complexes has changed the landscape of structural biology. The majority of structures deposited in the Electron Microscopy Data Bank (EMDB) at higher than 4-Å resolution were collected on Titan Krios microscopes. Although the pipeline for single-particle data collection is becoming routine, there is much variation in how sessions are set up. Furthermore, when collection is under way, there are a range of approaches for efficiently moving and pre-processing these data. Here, we present a standard operating procedure for single-particle data collection with Thermo Fisher Scientific EPU software, using the two most common direct electron detectors (the Thermo Fisher Scientific Falcon 3 (F3EC) and the Gatan K2), as well as a strategy for structuring these data to enable efficient pre-processing and on-the-fly monitoring of data collection. This protocol takes 3–6 h to set up a typical automated data collection session. This protocol describes a pipeline for data collection, pre-processing and on-the-fly analysis for single-particle cryo-electron microscopy using EPU software and two direct electron detectors: the Thermo Fisher Scientific Falcon 3 and the Gatan K2.